Corporate Governance Failures in State‑Owned Enterprises: Evidence from the Aviation Sector - Matuza, Tatenda; Mita, Aria Farah (Journal of Economics and Business UBS, 2025)
Governance weaknesses continue to persist in Country X’s state-owned aviation enterprise despite the presence of robust statutory frameworks governing public financial management and corporate accountability. This study aims to examine the underlying factors that contribute to the continued failure of governance implementation and to analyze how forensic accounting mechanisms can strengthen accountability and oversight. A qualitative case study approach was employed, utilizing in-depth interviews with policymakers, external auditors, and internal control personnel. These primary data were triangulated with secondary sources, including supreme audit institution reports, internal governance documents, and relevant governance statutes such as PFM-X and PEG-X. The findings reveal three key issues underlying persistent governance failures: selective enforcement of statutory regulations, centralized oversight structures with limited effectiveness, and uneven internal control systems—strong in payment authorization but weak in procurement processes, asset management, and record-keeping practices. Furthermore, political interference and limited digital traceability exacerbate the gap between formal regulations and actual implementation. The study concludes that embedding forensic accounting tools—such as digital audit trails, trigger-based investigative reviews, and continuous auditing systems—can significantly enhance transparency, deter misconduct, and shift compliance from procedural formality to substantive enforcement. These findings highlight the strategic role of forensic accounting in improving governance quality and accountability outcomes within state-owned enterprises, particularly in complex and politically influenced sectors such as aviation.